Computer aided morphometric analysis of oral leukoplakia and oral squamous cell carcinoma. (18th May 2016) - Gupta, K; Gupta, J; Miglani, R
Abstract : We compared the changes in the cells in the basal layer of normal mucosa, oral leukoplakia with dysplasia and different grades of oral squamous cell carcinoma (OSCC) using computer aided image analysis of tissue sections. We investigated three morphometric parameters: nuclear area (NA), cell area (CA) and their ratio (NA:CA). NA and NA:CA ratio showed a statistically significant increase from dysplasia to increasing grades of OSCC. Nuclear size was useful for differentiating normal tissue, potentially malignant leukoplakia and OSCC.